Temperament and School Readiness – A Literature Review - Potmesilova, Petra; Potmesil, Milon (Frontiers in Psychology, 2021)
This review study was conducted to describe how temperament is related to school readiness. The basic research question was whether there is any relationship between later school success and temperament in children and, if so, what characterizes it. A systematic search of databases and journals identified 27 papers that met the two criteria: temperament and school readiness. The analytical strategy followed the PRISMA method. The research confirmed the direct relationship between temperament and school readiness. There is a statistically significant relationship between temperament and school readiness. Both positive and negative emotionality influence behaviour (especially concentration), which is reflected in the approach to learning and school success.